Evaluation of the Program for Giving Iron Supplementary Tablets to Young Girls in Schools at the Work Area of the Kunto Darussalam Public Health Center in 2022 - Rika Fitri Yanti*; Kiswanto Kiswanto; Agus Alamsyah (Universitas Syiah Kuala, 2023)
The program for giving iron tablets to young women at school is one of the government's programs as an effort to overcome anemia in young women. The UPTD of the Kunto Darussalam Health Center has carried out a program for giving iron tablets to young women at school, but the coverage for iron supplements is still low, namely 45.7%. The aim of the study was to evaluatethe program for giving iron supplementary tablets to young girls in schools at the Work Area of the Kunto Darussalam Public Health Center 2022 using the CIPP method with input, process and product (output) context indicators. This type of research is qualitative with a phenomenological research approach. There were 12 informants consisting of nutrition program holders from the Rokan Hulu District Health Office, the person in charge of the UPTD Nutrition Program at the Kunto Darussalam Health Center, midwives, nurses, school principals, UKS teachers, young women and parents. The triangulation used is the triangulation of sources, methods and data. The results of the study show that the context (needs, problems, assets and opportunities) has been identified, inputs (human resources, funding, Posbindu PTM facilities and infrastructure) and processes ((preparation, distribution and delivery, recording and reporting,Ironsupplement tables. Community Health Centers can facilitate the formation of Rematri ambassadors and digital-based educational innovations through the peer-group “Ayo CERIA” establishing partnerships in every village through Corporate Social Responsibility and involving the private sector in the procurement of facilities and infrastructure